OC-104 The validity of the royal college of pathologists' stomach cancer minimum dataset in a population using the Northern & Yorkshire cancer registry data. (28th May 2012) - Rotimi, O; Grabsch, H; Morris, E
Abstract : Introduction: Quality histopathological reporting of resceted stomach cancer provides important information for treatment of patients. Sub-standard reporting leads to incorrect staging which impacts on treatment and ultimately survival. Proforma reporting has been introduced as a means of standardisation. This study sought to validate the prognostic significance of the Royal College of Pathologists (RCPath) stomach cancer dataset 1 in a population. Methods: A retrospective analysis of pathology forms from 1065 resected stomach cancer from 1995 to 2006 was carried out. The variables reported were related to NYCRIS registry survival data using univariate Kaplan–Meier method and Cox proportional regression modelling. Results: The study population was representative of the Yorkshire stomach cancer population. Survival was poorer with increasing age but it improved significantly from 29.0% (95% CI 23.1% to 35.1%) in 1995–1997 period to 50.5% (95% CI 40.1% to 60.1%) in the 2004–2006 period. Depth of local invasion, nodal stage and completeness of excision are validated as independent prognostic factors in a population setting. Importantly tumour differentiation is shown to be an independent prognostic factor. Patients recorded as well differentiated tumours had significantly better 3-year survival (61.3%; 95% CI 53.2% to 68.4%) compared to moderate (38.4%; 95% CI 33.2% to 43.6%) and poor differentiation (34.1%; 95% CI 30.1% to 38.1%)—Abstract OC-104 figure 1 . The effect remains significant after adjusting for age and gender with HR of 1.74 (95% CI 1.11 to 2.71) for moderately differentiated and 2.1 (95% CI 1.3 to 3.4) for poorly differentiated tumours compared to well differentiated tumour. Conclusion: The variables in the RCPath stomach cancer dataset are validated to be of prognostic significance in a population setting. Importantly, the result showed that there is a significant survival differences between the three grades of differentiation. This is in contrast to the current recommendation by the RCPath that well and moderately differentiated tumours be reported together as a single category. 1 We recommend separating this category in the next version of the RCPath stomach cancer dataset guidelines. Competing interests: None declared. Reference: 1. Novelli M . Dataset for the Histopathological Reporting of Gastric Carcinoma. Standards and Datasets for Reporting Cancers . 2nd edn. The Royal College of Pathologists. 2007.